Birt-Hogg-Dubé syndrome in Korean: clinicoradiologic features and long term follow-up - Joo Hee Lee; Min Joo Jeon; Joon Seon Song; Eun Jin Chae; Jin-Ho Choi; Gu-Hwan Kim; Jin Woo Song (The Korean Journal of Internal Medicine, 2019)
Background/Aims Birt-Hogg-Dubé (BHD) syndrome is a rare autosomal dominant disorder that is characterized by skin fibrofolliculomas, pulmonary cysts, and renal tumors. The objective of this study was to describe the features of Korean patients with BHD syndrome. Methods Clinical data were retrospectively reviewed in 12 patients (10 confirmed by direct sequencing of the folliculin (FLCN) gene and two confirmed by clinical diagnosis) diagnosed from 2004 to 2016 at Asan Medical Center, Seoul, South Korea. Criteria proposed by the European BHD consortium were used for diagnosis. Results The median follow-up was 52 months. The mean age was 41.3 years and 66.7% were female. Eight patients (66.7%) had a history of pneumothorax, which was recurrent in 75%. Skin lesions were detected in 25.0% and renal cancer in 25.0%. Among mutations of the FLCN gene, the duplication of cytosine in the C8 tract of exon 11 (c.1285dupC) was the most common (40%); however, a novel heterozygous sequence variant of c.31T>C (p.C11R) in exon 4 was detected in one patient. All patients had multiple and bilateral pulmonary cysts, distributed in predominantly lower, peripheral and subpleural regions of the lungs. Most patients showed preserved lung function that remained unchanged during follow-up, and two (16.7%) developed cancers (renal cancer in one and breast cancer in one). Conclusions Our data suggest that Korean patients with BHD syndrome may have a higher risk of pneumothorax, less frequent skin lesions, and a novel FLCN mutation compared to previous reports. Multiple bilateral and basal-predominant cysts were the most common radiologic features.